Conceptual and Procedural Trajectories in Transformation Geometry: A Comparative Study of Technology-Enhanced and Conventional Van Hiele Phased Instruction - Ndungo, Issa; Balimuttajjo, Sudi; Akugizibwe, Edwin (International Journal of Education, Technology and Science, 2025)
This study investigates the effectiveness of Technology-Enhanced Van Hiele Phased Instruction (TVHPI) compared to Conventional Van Hiele Phased Instruction (CVHPI) in enhancing learners' conceptual understanding and procedural fluency in transformation geometry. A quasi-experimental design was employed, involving 144 secondary school learners from six schools in Uganda. Conceptual and procedural understanding was assessed from learners’ test scripts using a 5-point scale of performance, and performance across Van Hiele levels was analyzed using descriptive and inferential statistics. Results revealed that TVHPI significantly improved both conceptual understanding (t = 10.861, p = 0.00) and procedural fluency (t = 10.491, p = 0.00) compared to CVHPI. Performance across Van Hiele levels showed foundational tasks (Levels 1 and 2) were better supported by both strategies, while TVHPI showed an advantage at intermediate levels (Level 3). The study recommends integrating technology like GeoGebra into instructional practices to enhance learning outcomes. These findings emphasize the potential of technology-enhanced strategies to improve geometric reasoning and inform curriculum design.
This study examined the impact of TVHPI on learners' conceptual understanding, procedural fluency, and performance across Van Hiele levels of geometric reasoning compared to CVHPI. The findings revealed that TVHPI significantly enhances both conceptual and procedural learning outcomes, offering a dynamic, interactive environment for engaging with geometric concepts. At foundational Van Hiele levels, both instructional strategies proved effective; however, TVHPI demonstrated a slight procedural advantage at intermediate levels, while CVHPI marginally supported complex reasoning at advanced levels.